2014
DOI: 10.1097/hjh.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between red blood cell distribution width and early-stage renal function damage in patients with essential hypertension

Abstract: RDW, as an easy and quick measurable index, can predict early-stage renal function damage in essential hypertensive patients without receiving drug treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
0
25
2
Order By: Relevance
“…This value is very close to that from published study that RDW was associated with MAU in hypertension patients without treatment. 24 Bulum et al found significant associations between RBC and renal function parameters in type 1 diabetic patients even with normal renal function (eGFR460 mL/min and urinary albumin excretion rate530 mg/24 h), suggesting that the interplay between RBC and renal function exists in the absence of nephropathy in type 1 diabetes. Those patients in the highest quartile of albuminuria in normoalbuminuric range had significantly higher Hb and Hct suggesting that it can be even prognostic factor for MAU.…”
Section: Discussionmentioning
confidence: 99%
“…This value is very close to that from published study that RDW was associated with MAU in hypertension patients without treatment. 24 Bulum et al found significant associations between RBC and renal function parameters in type 1 diabetic patients even with normal renal function (eGFR460 mL/min and urinary albumin excretion rate530 mg/24 h), suggesting that the interplay between RBC and renal function exists in the absence of nephropathy in type 1 diabetes. Those patients in the highest quartile of albuminuria in normoalbuminuric range had significantly higher Hb and Hct suggesting that it can be even prognostic factor for MAU.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present study included larger sample sizes than previous study. Li et al 16 found that RDW level was related to early renal injury in patients with hypertension, which was the first study about relationship between RDW and early-stage renal injury. The present study further confirmed and extended these findings and provided stronger support about the role of RDW in target-organ injury of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…15 Li et al 16 found that RDW level was associated with early renal injury in hypertensive patients, which was the first study about relationship between RDW and renal injury. The patients with renal injury tend to be higher RDW level.…”
Section: Introductionmentioning
confidence: 99%
“…[2931] Li et al [29] reported that there is a positive correlation between RDW and albumin-to-creatinine ratio in hypertensive patients. Zhang et al [30] reported that RDW was an independent risk factor of microalbuminuria in patients with newly diagnosed type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%